The reflection paedagogy of Vasyl Sukhomlynsky and Janusz Korczak - ŚLIWERSKI, BOGUSŁAW (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Bogusław Śliwerski, The reflection paedagogy of Vasyl Sukhomlynsky and Janusz Korczak. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 99–115. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.05 The subject of the analysis is the paedagogical thought of the leading representatives of the new education movement in Poland and in the Ukraine. The timeless character of their reflection paedagogy was exemplified by the orphans’ home of Warsaw, Poland, and the School of Joy in Pavlysh, Ukraine, the organisational solutions, rules of (self-)education, the system of social and moral standards bound educators the same way as they did those under their care. The phenomenon of the radical, unique approaches to supporting children, which they created, is a challenge for coming generations. With this work, I also open up the debate and the need for further research concerning the origins and consequences of transgression of state borders by paedagogical thought that constantly changes its approach to humanist paidocentric paedagogy in a world, in which authoritarian, directive or instrumental paedagogy continues to have a strong presence. In this regard, I focus primarily on the similarity of thought between both these educators, indicating the differences in their approach to the child.